Olympism and Positive Youth Development (PYD): A New Goal in The Extension of Youth Sports Development for Basketball in Indonesia - Rismayadi, Alen; Subarjah, Herman; Yudiana, Yunyun; Rusdiana, Agus (Universitas Pendidikan Indonesia, 2020)
The basic principle of Olympism aims to make sport as a harmonious human development tool to create a peaceful society and to respect human dignity. The purpose of this study was to investigate the Olympism values in the context of a positive development of the youth, as well as the historical journey of basketball development including the competition system which has been running before. The research method used was descriptive method by employing document review and semi-structured interviews as the instruments to obtain data. The results of this study revealed how the basic principles of Olympism are applied as an approach in basketball coaching in the context of the positive development of youth. The responses of parents, builders, and coaches regarding the new approach in the basketball coaching system are explored and discussed deeply.